2017
DOI: 10.1111/imb.12327
|View full text |Cite
|
Sign up to set email alerts
|

Dusky works upstream of Four‐jointed and Forked in wing morphogenesis in Tribolium castaneum

Abstract: Dusky (dy) is required for cytoskeletal reorganization during wing morphogenesis in Drosophila melanogaster, but which genes participate together with dy for wing morphogenesis has remained unclear. In Tribolium castaneum, dy is highly expressed at the late embryonic stage. Tissue-specific expression analysis indicated high expression levels of dy in the epidermis, head and fat body of late-stage larvae. RNA interference (RNAi) targeting dy significantly decreased adult wing size and caused improper folding of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
21
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(24 citation statements)
references
References 50 publications
(75 reference statements)
1
21
0
Order By: Relevance
“…However, the mechanism by which chitin-degrading genes control the development of wings remains unclear. Previous studies demonstrated that these genes, such as dusky (DY), wingless (WG), vestigial (VG), and apterous (AP), have essential roles during the wing morphogenesis of T. castaneum [62,63]. Here, we found that the expression levels of LsDY, LsWG, LsVG, and LsAP were downregulated after the knockdown of LsCDA1 in L. serricorne.…”
Section: The Function Of Lscda1 Involved In Wing Development During Pmentioning
confidence: 67%
“…However, the mechanism by which chitin-degrading genes control the development of wings remains unclear. Previous studies demonstrated that these genes, such as dusky (DY), wingless (WG), vestigial (VG), and apterous (AP), have essential roles during the wing morphogenesis of T. castaneum [62,63]. Here, we found that the expression levels of LsDY, LsWG, LsVG, and LsAP were downregulated after the knockdown of LsCDA1 in L. serricorne.…”
Section: The Function Of Lscda1 Involved In Wing Development During Pmentioning
confidence: 67%
“…Furthermore, 95.93 ± 0.15% of ds‐ forked adults died 7 days after eclosion (Figure d). Singed and miniature silencing showed different effects from those of crinkled RNAi (Li, Li, Ma, Lu, & Chen, ).…”
Section: Resultsmentioning
confidence: 99%
“…One possible reason for this is that RNAi on svb deleted more mRNA levels of itself than that by crinkled knockdown (Figure b; Li et al., ). The transcription of svb was regulated by a number of genes in the insect (Chanut‐Delalande et al., ; Li et al., ; Payre et al., ), and the roles of svb in pupation, eclosion, and epidermal pigmentation are mainly controlled by other genes not crinkled . Downstream genes of svb likely mediate the function of crinkled in wing morphogenesis in the insect.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations